A revision of the New World genus Ceraeochrysa (Neuroptera: Chrysopidae). - de Freitas, Sergio; Penny, Norman D.; Adams, Phillip A. (My University, 2009)
The sixty-four known species of Ceraeochrysa Adams, 1982 are described, illustrated, and GEOGRAPHICAL DISTRIBUTIONS given. A preliminary phylogeny of the species is presented. Eleven species are newly described (C. achillea, C. angusta, C. beliaensis, C. bitacornua, C. chiricahuae, C. curvabilis, C. digitata, C. derospogon, C. diverticula, C. forcipata, and C. panamensis). Two species are returned to this genus (C. laufferi and C. placita). Three names are synonymized: Chrysopa silvestrina Navas, 1929 = Ceraeochrysa cincta (Schneider, 1851); Chrysopa gradata Navas, 1913 = Ceraeochrysa effusa (Navas, 1911); and Chrysopa aroguesina Navas, 1929 = Ceraeochrysa laufferi (Navas, 1922). Two new lectotype designations are indicated: Chrysopa cincta Schneider, 1851 and Chrysopa valida Banks, 1895. New status is given to Ceraeochrysa parvula (Banks, 1903).